2020
DOI: 10.1101/2020.02.18.954347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic transcriptional reprogramming by WT1 mediates a repair response during podocyte injury

Abstract: In the context of human disease, the mechanisms whereby transcription factors reprogram gene expression in response to injury are not well understood. This is particularly true in kidney podocytes, injury to which is the common and initial event in many processes that lead End Stage Kidney Disease. WT1 is a master regulator of gene expression in podocytes, binding nearly all genes known to be crucial for maintenance of the glomerular filtration barrier. Here, using purified populations of podocytes and glomeru… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…To determine which cell types are responding to infused Ang II by inducing FGFR1 phosphorylation, we colocalized FGFR1 with different cellular markers in mouse kidneys. Specifically, we marked renal epithelial cells with AQP1 (aquaporin 1), 17 podocytes with WT1 (Wilms tumor 1), 18 endothelial cells by VE-cadherin, and mesangial cells by SMA (smooth muscle actin). Our results show that FGFR1 immunoreactivity mainly colocalizes to AQP1-expressing cells (Figure 3A; Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…To determine which cell types are responding to infused Ang II by inducing FGFR1 phosphorylation, we colocalized FGFR1 with different cellular markers in mouse kidneys. Specifically, we marked renal epithelial cells with AQP1 (aquaporin 1), 17 podocytes with WT1 (Wilms tumor 1), 18 endothelial cells by VE-cadherin, and mesangial cells by SMA (smooth muscle actin). Our results show that FGFR1 immunoreactivity mainly colocalizes to AQP1-expressing cells (Figure 3A; Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…Ildr2/ILDR2 is found to be specifically expressed in mouse and human podocytes as observed from publicly available databases including KIT (Wu et al, 2018;Wu et al, 2019), and MS identified it in proteomic analyses of whole podocytes (Rinschen et al, 2018). Ildr2 was also identified as a Wt1 transcriptional target in podocytes by ChIP-seq (Ettou et al, 2020). However, none of these studies noted the expression of Ildr2 or interrogated its localization within the kidney or podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…44, 58 Ildr2 was also identified as a Wt1 transcriptional target in podocytes by ChIP-seq. 59 In early embryonic and postnatal mouse kidneys, Ildr2/ Ildr2 is expressed and localized to tubule cells and podocytes. However, in the adult kidney Ildr2 localization becomes restricted to podocytes.…”
Section: Discussionmentioning
confidence: 99%